2021
DOI: 10.30607/kvj.849190
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carprofen Treatment on Conception Rate After Insemination in Cows with Increased Days in Milk

Abstract: In this study the effect of carprofen treatment on conception rate after insemination in Holstein cows that did not conceive for a long time after parturition was evaluated. In the study, 200 Holstein cows with days in milk >120 were used. A progesterone + ovsynch-based estrus synchronization protocol was applied to the cows included in the study. For this purpose, the progesterone device was placed intravaginally together with GnRH injection. Seven days later, the progesterone source was removed from the vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Although an increase in pregnancy rates was observed with post‐mating double‐dose diclofenac application in goats (Aksu, 2019; Doğruer et al, 2012), no increase was observed in pregnancy rates in our study in ewes. Previous studies of carprofen treatment in dairy cows have reported varying degrees of positive responses differing from 12% (Özkök, 2019) to 17% (Alkan et al, 2021) in pregnancy rate. While some others have reported decrease at about 2.5% to 10% (Heuwieser et al, 2011; Satılmış et al, 2020; Von Krueger & Heuwieser, 2010), compared to the controls.…”
Section: Discussionmentioning
confidence: 98%
“…Although an increase in pregnancy rates was observed with post‐mating double‐dose diclofenac application in goats (Aksu, 2019; Doğruer et al, 2012), no increase was observed in pregnancy rates in our study in ewes. Previous studies of carprofen treatment in dairy cows have reported varying degrees of positive responses differing from 12% (Özkök, 2019) to 17% (Alkan et al, 2021) in pregnancy rate. While some others have reported decrease at about 2.5% to 10% (Heuwieser et al, 2011; Satılmış et al, 2020; Von Krueger & Heuwieser, 2010), compared to the controls.…”
Section: Discussionmentioning
confidence: 98%
“…Carprofen is a long effective NSAID with a clinical effect of 12 h. It has a small volume of distribution much longer plasma elimination half-life (30 to 40 h) in cattle than FM and is poorly excreted in milk [ 43 ]. Administration of CAR had no significant effect on the concentration of plasma progesterone or on embryo mortality [ 44 ], and when administered during the critical period of pregnancy, i.e., on the 14th and 15th Day after insemination, did not have a significant effect on the pregnancy rate in cows [ 16 , 45 , 46 ]. In cows (>120 days in milk), receiving CAR subcutaneously 14 days after timed AI, the PR ( p < 0.05) was 42.26% compared to 25.26% in the control group.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…It is also worth of noting that in high-yield cows (>30 kg of milk per day), the PR was much lower (10.52%). The conclusion was that administration of CAR on the 14th Day after insemination to cows who could not conceive for a long time after parturition may be effective in increasing the rate of conception [ 46 ]. In the latest experiment of Abay et al [ 47 ], CAR administration 14 days after AI improved chances ( p < 0.05) of maintaining the CL in females with body condition score (BCS) ≤ 2.5 (81.7 vs. 70.7% respectively for CAR and control group), whereas for animals with BCS > 2.5 CAR treatment decreased CL maintaining chances compared to the control (74.5 vs. 90.5%, respectively, p < 0.05).…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%